Annual Report 2020 of Current Applied Science and Technology - Thanaboripat, Dusanee (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2021)
Current Applied Science and Technology (CAST) journal, formerly KMITL Science and Technology Journal, has been published by King Mongkut’s Institute of Technology Ladkrabang (KMITL) since its inception as KMITL Science Journal in 2001. In 2010 the journal was published in both print and electronic forms starting from volume 10. Since July 2017 the journal title has been changed to Current Applied Science and Technology and printed online only. In 2018 CAST journal was submitted to Scopus database on 3 December via TCI-TRF-Scopus Collaboration Project and the journal was accepted to be indexed in Scopus on 14 January 2019. CAST journal is currently under the responsibility of the Office of Academic Journal Administration, President’s Office, KMITL, which is a newly established office founded on 25 February 2020. At present CAST journal is indexing in Scopus, ACI (ASEAN Citation Index), TCI (Thai Citation Index) Tier 1 and Scimago Journal Rank (SJR): Q4. The journal is an open access peer-reviewed and double blinded journal. Aims and scope of the journal are to provide a platform for researchers, scientists and academicians to share knowledge and ideas in the form of high-quality articles covering the main fields of Biotechnology, Environmental Science, Agricultural Technology, Food Science and other fields related to Applied Science and Technology. Special issues devoted to important topics in advanced science and technology will occasionally be published. There is no page charge for submission and all articles can be freely downloaded from the journal website: https://li01.tci-thaijo.org/index.php/cast.